2017
DOI: 10.1002/eco.1879
|View full text |Cite
|
Sign up to set email alerts
|

Litter is more effective than forest canopy reducing soil evaporation in Dry Chaco rangelands

Abstract: Soil evaporation is a dominant water flux of flat dry ecosystems, reducing available water for plant transpiration. Vegetation plays a key role at controlling evaporation, especially by altering soil surface micro‐meteorological conditions. Here, we explored the vegetation cover effect on soil evaporation, differentiating the effects of canopy cover (shadow) and of surface cover (litter) in forests and pastures of Dry Chaco rangelands (San Luis, Argentina). We measured daily soil evaporation using irrigated mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 75 publications
0
19
0
2
Order By: Relevance
“…Throughfall dripping from the canopy may concentrate water in a few points infiltrating deeper into the soil profile F I G U R E 5 Interception loss (a, b), throughfall (c, d) and stemflow (e, f) as a function of rainfall event size and intensity reducing evaporation losses and enhancing plant consumption (Fan et al, 2015;Loik, Breshears, Lauenroth, & Belnap, 2004;Magliano, Giménez, et al, 2017). Different studies have explored the relationship between throughfall fluxes and the distance from the stem-soil intersection to the periphery of the canopy, assuming that large throughfall inputs that infiltrate close to the base of stems and trunks may represent a benefit for the plants (similarly to stemflow localized inputs) (Loustau et al, 1992;Shachnovich et al, 2008;Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Throughfall dripping from the canopy may concentrate water in a few points infiltrating deeper into the soil profile F I G U R E 5 Interception loss (a, b), throughfall (c, d) and stemflow (e, f) as a function of rainfall event size and intensity reducing evaporation losses and enhancing plant consumption (Fan et al, 2015;Loik, Breshears, Lauenroth, & Belnap, 2004;Magliano, Giménez, et al, 2017). Different studies have explored the relationship between throughfall fluxes and the distance from the stem-soil intersection to the periphery of the canopy, assuming that large throughfall inputs that infiltrate close to the base of stems and trunks may represent a benefit for the plants (similarly to stemflow localized inputs) (Loustau et al, 1992;Shachnovich et al, 2008;Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This contrasting behaviour is probably due to the fact that some of the dry forest species have deeper root systems (Canadell et al, 1996; Marchesini et al, 2013) than the pasture that would allow them to use deeper water (Jobbágy, Nosetto, Villagra, & Jackson, 2011) and sustain a certain carbon gain during rainless periods. There are three main mechanisms that favour water storage at greater depth in the studied dry forest, which include (i) run‐off/run‐on water redistribution that concentrates rainfall and favours percolation in a minor fraction of the area (Magliano, Breshears, Fernández, & Jobbágy, 2015; Magliano, Fernández, Florio, Murray, & Jobbágy, 2017), (ii) large amounts of stemflow generation by some dominant shrubs such us Larrea divaricata (Magliano, Whitworth‐Hulse, Florio, Aguirre, & Blanco, 2019) and (iii) the low atmospheric demand at the soil surface level caused by canopy shade and litter that maintains wet soil conditions increasing the probability that the next rain event reaches greater depths (Magliano et al, 2017). In addition, deep soil layers (>1 m) under dry forests of the region are typically salty because of long‐term accumulation of atmospheric salts resulting from an exhaustive use of rainfall inputs by plants (Santoni, Jobbágy, & Contreras, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is necessary to understand how individual plant species in tropical environments use different water sources. Water uptake by tropical trees is linked to leaf phenology and transpiration rates (Schwendenmann et al, 2015); however, the use of stable isotopes in xylem water could by affected due to evaporative fractionation during the transport within the plant tissues (Barbeta et al, 2019;Martín-Gómez et al, 2016;Zhao et al, 2016) or selective acquisition (Vargas et al, 2017). This evidence depicts the need to better understand the effect on stable water isotope signatures during the water transport within the plant.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence has shown that tree species such as Pinus sylvestris L., Quercus subpyrenaica Villar, Persea americana Mill., Fagus sylvatica L. and Populus euphratica Oliv. are able to fractionate the isotope signatures of xylem water (Barbeta et al, 2019;Martín-Gómez et al, 2016;Vargas et al, 2017;Zhao et al, 2016). This raises the question of whether tropical trees modify the isotope signature of xylem water, as a response to their plasticity to seasonal changes despite their similar root distribution (Schwendenmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%